Preferencje młodych klientów banków w zakresie bankowości internetowej - Sołtysiak, Mirosław (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The article presents selected outcomes of research concerning awareness andpreferences of young Poles with respect to online banking. The study was carriedout in 2013–14 on a sample of students from Podkarpackie voivodeship.The analysis of the research outcomes allowed to assess the level of significanceof online banking services for young people and to specify factors relevant forchoosing a bank or online banking service.